Modeling the impact of innovation in marine energy generation-related technologies on carbon dioxide emissions in South Korea. (15th January 2023) - Jiang, Qingquan; Khattak, Shoukat Iqbal
Abstract: South Korea has invested extensively in developing revolutionary marine and ocean technologies to accomplish renewable energy goals. Despite that, the available literature offers no insight into the environmental benefits of innovation in marine energy generation, distribution, or transmission-related technologies (IMET). This study examines the nexus between carbon dioxide emissions (CO2 e) and IMET in South Korea (1990Q1-2018Q4). Control variables include international collaboration in green technology development (ICGD), gross domestic product (per capita) (GDPPC), expansionary commercial policy (ECP), and renewable energy use (REC). First, the findings validated the long-run relationship among ICGD, GDPPC, ECP, REC, IMET, and CO2 e. Second, the findings asserted that increasing IMET assisted in the generation of low-carbon renewable energy, thereby contributing to the improvement of environmental quality. Third, the estimates revealed that an increase in GDPPC and ECP was positively associated with an upsurge in CO2 e. Fourth, the data depicted that ICGD facilitated co-green technologies development, which de-escalated CO2 e. Fifth, REC was negatively associated with a decrease in CO2 e. Based on current estimates, this article recommended that governments implement policies that encourage companies and academia to participate in IMET to promote the green economy. Highlights: A rise in innovation in marine energy generation-related technologies was negatively associated with CO2 emissions. An increase in GDP per capita and expansionary commercial policy contributed to CO2 emissions. International collaboration in environmental-related technology development reduced CO2 emissions. Renewable energy consumption deescalated carbon dioxide emissions.